MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA MENGGANTUNG MELALUI MEDIA KARET GELANG PADA SISWA SD - Riyanto, Ahmad; Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: A common problem in this research is how long jump effort to improve skills hang style by using teaching aids in the form of a rubber band. The research objective was to determine the improvement of learning outcomes in the long jump leap through the medium of a rubber band on the students.The method used in this research is descriptive method with the application of classroom action research is conducted through two cycles to see and improve learning outcomes long jump style by using the media to hang a rubber band. The subjects with a total of 27 students.Value - average ratings in the first cycle was 67.96, with 74% of students with values ≥65 and 26% of students with values <65. In the second cycle the average - average assessment of students is 74.07, with 100%students with values ≥65 and 0% of students with values <65. Keywords: long jump, rubber bands, hangingstyle.